Respuesta :

Answer:

[tex]n = 8[/tex]

Step-by-step explanation:

[tex]3n - 2(n + 8) = - 8[/tex]

[tex]3n - 2n - 16 = - 8[/tex]

[tex]n - 16 = - 8[/tex]

[tex]n = - 8 + 16[/tex]

[tex]n = 8[/tex]

#IfWrongPleaseReport

#StudyTogetherWithMe

#ILoveMath

Answer:

n=8

Step-by-step explanation:

Step 1: Simplify both sides of the equation.

3n−2(n+8)=−8

3n+(−2)(n)+(−2)(8)=−8(Distribute)

3n+−2n+−16=−8

(3n+−2n)+(−16)=−8(Combine Like Terms)

n+−16=−8

n−16=−8

Step 2: Add 16 to both sides.

n−16+16=−8+16

n=8

ACCESS MORE